Delimitação da zona de amortecimento do Parque Estadual Pedra da Boca, Araruna-PB : proposta de setorização e recomendações de uso - Guimaraes, Yasmin Cynara de Oliveira (2022)
Protected areas in Brazil, governed by Law No. 9.985/2000, have legal instruments that aim to effect environmental preservation. Among them, we mention the buffer zone, an important legal instrument for environmental preservation, widely discussed in this dissertation. The Pedra da Boca State Park, which is located in the municipality of Araruna - PB, created on February 7, 2000 through state decree n° 20.889, until the completion date of this research still does not have all its legal instruments created and among them, the buffer zone stands out. The Park presents in its landscape a complex of rocky outcrops of great grandeur and scenic beauty, characteristics of fundamental influence for its creation as a conservation unit. In this context, the objective is to present a proposal for a buffer zone for the aforementioned Park, in accordance with the current resolution that points out directions on it, CONAMA 482/2011, where it is specified that the said zone must correspond to a radius of three kilometers. starting from the delimitation of the conservation unit in question. After the delimitation, it is proposed the sectorization of this area, in order to quantify and spatialize the existing homologous zones that are similar in landscape, or that perform the same function. In addition to these sectors, it was interesting to use the data available in the Rural Environmental Registry referring to springs, permanent preservation areas, legal reserves and native vegetation, given the fact that these areas existed beforehand and specific legislation, that is, the Forest Code for its treatment, the existence of an overlap of areas and legal instruments with different purposes is highlighted here. Subsequently, a diagnosis aimed at conflicting uses present in the area is proposed in order to build specific recommendations based on what already exists in the literature for each identified sector, aiming at the effectiveness of the function of the buffer zone, which corresponds to minimizing the impacts that may fall on the conservation unit. It should be noted that the purpose of the recommendations is not limited to restrictions, but the conscious use of the area. The diagnosis will guide the construction of recommendations, aimed at meeting social, economic and environmental aspects in order to establish a beneficial and balanced relationship between these three areas. The spatialization of these recommendations generates a prognostic map, making it possible to visualize the area in case the recommendations are applied, in addition to classifying the sectors delimited in two different damping levels. Separating the areas into two levels of damping, they are the level that provides greater damping to the conservation unit, where the areas are classified by a lower level of human intervention and greater preservation of vegetation and ecosystems, and the second level of damping. greater anthropic intervention. This division into levels aims at greater care with specific areas, especially those that provide significant buffering to the matrix aiming at long-term work.